(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2016)
The present study specifically indicated that the crude ethanolic and aqueous extracts of the leaves of Adhatoda vasica Nees produced anthelmintic activity against african earthworm Eudrilus eugeniae. Various concentrations (10, 25, 50 mg/ml) of aqueous and ethanolic extracts were evaluated in the bioassay involving determination of time of paralysis (P) and time of death (D) of the worms. Albendazole was used as standard anthelmintic drug and distilled water was used as negative control. The results of the present study indicated that the ethanolic and aqueous extracts significantly exhibited paralysis of worms in lower doses (10, 25 and 50 mg/ml) and also caused death of worms at higher concentration of 50 mg/ml, as compared to standard drug. Further studies are in process to isolate the active principle responsible for the activity. Dhaka Univ. J. Pharm. Sci. 14(2): 153-155, 2015 (December)